Analysis of the Application of Geography Learning Strategies on Natural Disaster Mitigation Material in Class XI of SMA Negeri 1 Sei Rampah - Anisa Muftih; Rahmadayanti, Rahmadayanti; Sri Muthia Hasan; Angelina Setia Simamora; Eni Yuniastuti (Jurnal Multidisiplin Sahombu, 2024)
This study aims to evaluate the implementation of geography teaching strategies on the topic of disaster mitigation in Grade XI at SMA Negeri 1 Sei Rampah. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The research subjects included geography teachers and Grade XI students actively involved in the learning process. The findings revealed that teachers employed various teaching strategies, such as group discussions, case study analyses, and the use of digital learning media, to enhance students' understanding of disaster mitigation. Classroom observations indicated that these strategies effectively encouraged active student participation and improved their analytical skills in addressing disaster cases. However, challenges were identified, including limited technological facilities and insufficient instructional time. The study concluded that implementing diverse and contextual teaching strategies supports geography learning objectives, particularly in understanding disaster mitigation concepts. This research recommends improving technology-based learning facilities and providing training for teachers to optimize the strategies applied.